Svalbard rock ptarmigan: a first glimpse into parasite infections - Nielsen, Ólafur K.; Fuglei, Eva; Pedersen, Åshild Ønvik; Skírnisson, Karl (Polar Research, 2024)
Natural ecosystems are under stress due to climate change and impacts are especially prominent at high latitudes. Manifestations of these changes include northward shifts in the distribution of birds, phenological mismatches, improved survival of parasites in the environment and the arrival of new parasite vectors and intermediate hosts. We collected baseline data on parasite infections in the Svalbard rock ptarmigan (Lagopus muta hyperborea), which is endemic to two High Arctic archipelagos, by sampling 10 birds caught in September–October 2015 in Van Mijenfjorden, Spitsbergen. Five species were found, three endo- and two ectoparasites. The endoparasites included a nematode,Heterakissp. (prevalence 10%), and two species ofEimeria, all with direct life cycles. TheEimeriaspecies are provisionally calledEimeriasp. A and sp. B (prevalence 50% and 20%; mean intensity 1560 and 1850 oocysts per g faeces, respectively). Both show morphological similarities with known rock ptarmigan eimeriids, but further taxonomic research is needed to describe their phylogenetic relationships. The two ectoparasites, the ischnoceran chewing liceGoniodes lagopiandLagopoecus affinis, both showed 90% prevalence and a mean intensity of 18.3 and 5.6, respectively. The eimeriids are host specific, and the chewing lice are common parasites of closely related grouse species. On the basis of our knowledge of rock ptarmigan parasites,Heterakissp. is considered a generalist parasite. The parasite fauna of the Svalbard rock ptarmigan is impoverished compared with conspecific populations in other Arctic locations, such as Iceland and Greenland.